Editorial: theologies of the digital - Oorschot, Frederike van; Höhne, Florian (Cursor_, 2023)
Digitization is a sometimes radical, sometimes very subtle process of transformation in all areas of our social, church and personal lives. The Corona pandemic in particular has once again brought this home and led to a sharp increase in digital communication in many areas of life. Sound theoretical modeling and theological reflection often lag behind real developments and the imaginaries spun around them. What can theological reflection contribute to the analysis, conceptualization, and evaluation of the emerging logics and narratives of the digital age? Conversely, how is theology challenged to interrogate the way it thinks about particular issues?